Physical education teachers' wellbeing and its relation with gender - Jorge Both; Adriano Ferreti Borgatto; Carlos Augusto Fogliarini Lemos; Vitor Ciampolini; Juarez Vieira do Nascimento (Desafio Singular, 2018)
The objective of this study was to evaluate the relation between gender and physical education teachers' wellbeing in southern Brazil, considering the socio-environmental (job satisfaction) and individual (lifestyle) parameters. A total of 1653 teachers (741 men and 912 women) in the states of Paraná, Santa Catarina, and Rio Grande do Sul were surveyed. The instruments used for data collection were QVT-PEF and PEVI, as well as a socio-demographic and professional questionnaire. The results confirm findings concerning dissatisfaction of physical education teachers regarding remuneration, work conditions, job autonomy, work and total life space as well as an overload in women's daily lives. In relation to lifestyle, women showed better eating habits; however, they also showed lower levels of positive behaviour in the components of relationships, and stress control. Therefore, the authors point out to implementation of public policies to ensure more equitable treatment regarding gender issues in the work environment, as well as regarding physical education teachers' personal aspects.